Pengaruh Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. Semen Bosowa Maros - Rika Arianti; Andi Nuryadin; Nurdin Latif (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine how much influence the work environment (X) has on job satisfaction (Y) at PT SEMEN BOSOWA MAROS. This type of research is quantitative. The data source was obtained from the PT Semen Bosowa Maros Office and the object of the study was carried out by distributing questionnaires to employees. The sampling technique used was a saturated sample where the entire population was 94 respondents. The results of the respondent study were tested with validity tests, reliability tests, partial tests (t-tests) data analysis techniques included descriptive analysis and simple regression analysis. Based on the results of statistical analysis to test the significance of the influence of the work environment on job satisfaction using the t test, it can be seen in table 4.11 that the calculated t value is 29.728, with a significance level of 0.000. Because the calculated t> t table (29.728,> 1.986) or the significance of t <5% (0.000 <0.05), then based on a simple analysis between the independent variable (X) work environment and the dependent variable (Y) job satisfaction, these results indicate that the work environment has a positive and significant influence on job satisfaction.